Essential Oils from Etlingera elatior Inflorescence against α-Amylase and α-Glucosidase Inhibition - Syafni, Nova; Nofrizal, Nofrizal; Ismed, Friardi; Putra, Deddi Prima (Jurnal Mandala Pharmacon Indonesia, 2025)
The increasing number of diabetes mellitus cases every year is alarming for every country. More than 90% of the cases are type-2 diabetes mellitus. The range of diabetes mellitus patients is at a productive age, including in Indonesia. Type-2 diabetes mellitus can be managed by reducing postprandial glucose levels. The approach inhibits α-amylase and α-glucosidase enzymes. A preliminary study on the local edible plants in Solok district, Etlingera elatior, showed potential against the α-glucosidase enzyme by TLC-bioautography screening. The essential oils from the inflorescence of E. elatior were extracted by hydro-distillation. The analysis of components from the essential oils identified 20 compounds. GC-MS data showed that the highest abundance percentages were 1-dodecanol (39.79%), dodecanal (28.20%), α-pinene (13.11%), decanal (4.16%), and dodecanol acetate (2.75%). The inhibition against the α-glucosidase enzyme obtains the IC50 value of 73.95 and 67.55 ?g/mL for the essential oils and acarbose, respectively. The inhibition against the α-amylase enzyme obtains the IC50 value of 70.87 and 12.28 ?g/mL for the essential oils and acarbose, respectively. The essential oils from the inflorescence of E. elatior could inhibit α-amylase and α-glucosidase enzymes, even though the potential was lower than that of acarbose as a positive control.